Expanding the clinical and molecular spectrum of ATP6V1A related metabolic cutis laxa. - Vogt, Guido; El Choubassi, Naji; Herczegfalvi, Ágnes; Kölbel, Heike; Lekaj, Anja; Schara, Ulrike; Holtgrewe, Manuel; Krause, Sabine; Horvath, Rita; Schuelke, Markus; Hübner, Christoph; Mundlos, Stefan; et al. (J Inherit Metab Dis, 2020)
Several inborn errors of metabolism show cutis laxa as a highly recognizable feature. One group of these metabolic cutis laxa conditions is autosomal recessive cutis laxa type 2 caused by defects in v-ATPase components or the mitochondrial proline cycle. Besides cutis laxa, muscular hypotonia and cardiac abnormalities are hallmarks of autosomal recessive cutis laxa type 2D (ARCL2D) due to pathogenic variants in ATP6V1A encoding subunit A of the v-ATPase. Here, we report on three affected individuals from two families with ARCL2D in whom we performed whole exome and Sanger sequencing. We performed functional studies in fibroblasts from one individual, summarized all known probands' clinical, molecular, and biochemical features and compared them, also to other metabolic forms of cutis laxa. We identified novel missense and the first nonsense variant strongly affecting ATP6V1A expression. All six ARCL2D affected individuals show equally severe cutis laxa and dysmorphism at birth. While for one no information was available, two died in infancy and three are now adolescents with mild or absent intellectual disability. Muscular weakness, ptosis, contractures, and elevated muscle enzymes indicated a persistent myopathy. In cellular studies, a fragmented Golgi compartment, a delayed Brefeldin A-induced retrograde transport and glycosylation abnormalities were present in fibroblasts from two individuals. This is the second and confirmatory report on pathogenic variants in ATP6V1A as the cause of this extremely rare condition and the first to describe a nonsense allele. Our data highlight the tremendous clinical variability of ATP6V1A related phenotypes even within the same family.

Variants in EXOSC9 Disrupt the RNA Exosome and Result in Cerebellar Atrophy with Spinal Motor Neuronopathy. - Burns, David T; Donkervoort, Sandra; Müller, Juliane S; Knierim, Ellen; Bharucha-Goebel, Diana; Faqeih, Eissa Ali; Bell, Stephanie K; AlFaifi, Abdullah Y; Monies, Dorota; Millan, Francisca; Retterer, Kyle; Dyack, Sarah; et al. (Am J Hum Genet, 2018)
The exosome is a conserved multi-protein complex that is essential for correct RNA processing. Recessive variants in exosome components EXOSC3, EXOSC8, and RBM7 cause various constellations of pontocerebellar hypoplasia (PCH), spinal muscular atrophy (SMA), and central nervous system demyelination. Here, we report on four unrelated affected individuals with recessive variants in EXOSC9 and the effect of the variants on the function of the RNA exosome in vitro in affected individuals' fibroblasts and skeletal muscle and in vivo in zebrafish. The clinical presentation was severe, early-onset, progressive SMA-like motor neuronopathy, cerebellar atrophy, and in one affected individual, congenital fractures of the long bones. Three affected individuals of different ethnicity carried the homozygous c.41T>C (p.Leu14Pro) variant, whereas one affected individual was compound heterozygous for c.41T>C (p.Leu14Pro) and c.481C>T (p.Arg161). We detected reduced EXOSC9 in fibroblasts and skeletal muscle and observed a reduction of the whole multi-subunit exosome complex on blue-native polyacrylamide gel electrophoresis. RNA sequencing of fibroblasts and skeletal muscle detected significant >2-fold changes in genes involved in neuronal development and cerebellar and motor neuron degeneration, demonstrating the widespread effect of the variants. Morpholino oligonucleotide knockdown and CRISPR/Cas9-mediated mutagenesis of exosc9 in zebrafish recapitulated aspects of the human phenotype, as they have in other zebrafish models of exosomal disease. Specifically, portions of the cerebellum and hindbrain were absent, and motor neurons failed to develop and migrate properly. In summary, we show that variants in EXOSC9 result in a neurological syndrome combining cerebellar atrophy and spinal motoneuronopathy, thus expanding the list of human exosomopathies.
Keywords: Amino Acid Sequence; Animals; Atrophy; Base Sequence; Cerebellum; Child, Preschool; Exosome Multienzyme Ribonuclease Complex; Exosomes; Female; Fibroblasts; Gene Knockdown Techniques; Genetic Variation; Haplotypes; Humans; Infant; Male; Motor Neurons; Muscle, Skeletal; Pedigree; RNA-Binding Proteins; Spinal Cord; Zebrafish